Analysis of The Relationship Between Cognitive Style and Creativity of Pre-Service Physics Teachers - Busyairi, Ahmad; Harjono, Ahmad; Gunawan, Gunawan (Kappa Journal, 2023)
This research aims to examine the relationship between cognitive style and creativity of prospective physics teachers in terms of two domains of creativity, namely personality and product. This research is quantitative and descriptive. The population of this study was 60 prospective physics teachers who were studying at Mataram University, Indonesia with a sample size of 40 people selected using the Simple Random Sampling technique. The instruments used in this research consisted of the standard Group Embedded Figures Test (GEFT) instrument, the Creative Personality test instrument, and the product creativity observation sheet. GEFT is used to identify differences in the cognitive styles of prospective physics teachers. The Creative Personality test instrument is used to determine the creativity of prospective physics teachers in terms of the aspects of fluency, flexibility, originality, and elaboration. Meanwhile, the observation sheet is used to assess the creativity of prospective teachers in producing products in the form of learning media in terms of novelty, utility, aesthetics, and authenticity. The results of the data analysis show that there is a relationship between cognitive thinking and the creativity of prospective physics teachers. Prospective physics teachers who have the FI cognitive style tend to have a better Creative Personality compared to FD (FI=1.94 > FD=1.44). However, on the contrary, the creativity of products carried out collaboratively shows that the FD group tends to get a better creative score (FI=3.01 < FD=3.41).